Pengaturan Pertanggungjawaban Pelaku Penyalahgunaan Deepfakes Dalam Teknologi Kecerdasan Buatan Pada Konten Pornografi Berdasarkan Hukum Positif Indonesia - Muhammad Faqih; Enni Soerjati Priowirjanto (Publikasi Indonesia, 2022)
Deepfakes as a derivative subset of the use of artificial intelligence technology have the ability to manipulate images or videos that overlay faces on other people's bodies with the intention of creating new videos with false representations. Initially this deepfakes ability was used in filmmaking and has now been applied to the features of mobile applications, but in reality there is an abuse of its ability to make a video with pornographic content. In Indonesia, there have also been several cases of similar pornographic videos featuring Indonesian artists in their videos and have been spread on the internet. Indonesia itself does not have special regulations regarding artificial intelligence technology, only explicitly stated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). This study was structured using normative juridical methods, using library data collection procedures, and document study data collection techniques. The study was conducted to discuss the legal basis for violations that occur when someone (the perpetrator) abuses the ability of deepfakes to make a video with pornographic content according to Article 29 jo. Article 4 paragraph (1) and Article 35 jo. Article 9 of Law Number 44 of 2008 concerning Pornography is an act that is prohibited and accompanied by criminal sanctions as a form of criminal responsibility for the perpetrators.